Pengaruh Disiplin Kerja, Motivasi Kerja, Dan Budaya Organisasi Terhadap Kinerja Karyawan Di Pt Anhong Media International Kota Batam - Dendy , Fransiskus Sero; Tamba, Imelda; Nuraeni , Brigida Endah (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2025)
This study aims to analyze the influence of work discipline, work motivation, and organizational culture on employee performance at PT Anhong Media International Batam City. This study uses a quantitative approach with a survey method, and data collection through questionnaires to 45 respondents who are all employees of PT Anhong Media International, data processing in this study uses SPSS version 26. The results of data processing of work discipline variables found that the calculated t-value was 3.017 > ttable 1.679 with a significance level of 0.004 < 0.05, then Ho was accepted and Ha was rejected, so that work discipline had a positive and significant influence on employee performance. The work motivation variable has a calculated t-value of 0.578 < table 1.679 with a significance level of 0.567 > 0.05, then Ho is rejected and Ha is accepted, then work motivation does not have a positive and significant influence on employee performance. The organizational culture variable has a calculated t-value of 2.268 > table 1.679 with a significance level of 0.029 < 0.05, then Ho is accepted and Ha is rejected, then organizational culture has a positive and significant influence on employee performance. From the f test, it was found that the thef value for work discipline, work motivation, and organizational culture was 8.817 > ftable 2.81 with a significance level of 0.000 < 0.05. From the R2 test, it is known that work discipline, work motivation, and organizational culture contribute 39.2% to employee performance, while the remaining 60.8% is influenced by other factors that were not studied in this study.